HIGHER ORDER THINKING SKILL QUESTIONS IN READING COMPREHENSION EXERCISE OF “WHEN ENGLISH RINGS A BELL” TEXTBOOK (RETAIN, 2023)
The objective of this study were to analyze and identify the reading comprehension questions using tree level of higher order thinking skill (HOTS) of Bloom’s taxonomy revised in the English textbook “When English Rings a Bell” 8th grades of junior high school namely analyzing level (C4), evaluating level (C5), and creating level (C6) and classify the reading comprehension hots into four knowledge dimension. Using content analysis and descriptive qualitative method, this research explored the questions in the activities of reading comprehension to identify which reading comprehension questions regarding involvement in higher order thinking skill. The result of the research analysis showed that 41 HOTS question in reading comprehension exercises were found in the textbook, and the most dominant HOTS questions was analyzing level 48 reading questions, followed by evaluating level 13 questions and creating level only 8 reading questions. Furthermore, the result found that the most used knowledge dimension in reading questions was conceptual knowledge 29 questions.